Fiscal Design and the Location of Economic Activity - Ulrike Stierle-von Schütz (European Regional Science Association (ERSA), 2005)
In the process of economic integration regional production structures are about to change. Several studies analysed already trends of regional specialization in the European Union and attempted to figure out determinants of observed changes. In this context, up to date the role of the public sector and especially the impact of different fiscal designs as determinants of the change in production structures have been left aside. Advantages and shortcomings of decentralized government organization have been largely discussed theoretically within the last decades. Several empirical studies attempted to examine the impact of decentralization on national performance, e.g. economic growth and fiscal stability. This paper aims at linking these two subjects and analyzes the empirical relationship between regional specialization and fiscal decentralization for a panel of 15 Member States of the European Union, controlling for regional and other institutional determinants. The analysis shows that rather autonomous regions tend to diverse their production structure in order to insure against adverse supply shocks.
Keywords: 330